A study on microstructure and recrystallization kinetics on low deformed pure ETP copper. (December 2022) - Harshavardhana, N; Sundar Singh Sivam, SP; Kumar, Gulshan; Saxena, Ashish Kumar
The kinetics of microstructural changes plays a vital role in designing the material properties. There are various microstructural transformation phenomena such as recovery, recrystallization, and strain-induced boundary migration, which affect the properties of materials. This study aims to investigate the kinetics of low-strain deformed electrolytic tough pitch (ETP) copper (less than 23% reduction in thickness), where an optimum value of hardness and conductivity is obtained after heat treatment when compared with a high strain deformed sample. The activation energy values for the low deformed sample calculated from changes in hardness, conductivity, and microstructure are in the range of 39–99 kJ/mol, 30–90 kJ/mol, and 40–51 kJ/mol, respectively, which is low compared to high deformed values. Careful microstructural investigation of the low-strain deformed copper shows evidence of strain-induced boundary migration, whereas high strain deformed copper shows evidence of recrystallization. The strain-induced boundary migration plays an important role in "cleaning up" some of the deformed grains with a composite microstructure consisting of deformed grains that preserve high hardness, while some grains have low defect density which helps to obtain high conductivity after heat treatment.